Murottal al-qur'an therapy to reduce anxiety in patient with cervical cancer - Irsan, Ahmad; Ibad, Muhammad Rosyidul (JOURNAL OF Mental Health Concerns, 2025)
Background: Cervical cancer is the fourth most common cancer in women worldwide and is the leading cause of cancer deaths, especially in low- and middle-income countries. Cervical cancer patients often experience severe anxiety due to uncertainty about the treatment process and the risk of death. Anxiety management can be done pharmacologically or non-pharmacologically, one of which is through Al-Qur'an recitation therapy as a spiritual therapy that is believed to provide relaxation and calmness. Purpose: To determine the effectiveness of Al-Qur'an recitation therapy in reducing anxiety levels in cervical cancer patients. Method: A case study of one stage IIIB cervical cancer patient selected through purposive sampling. Al-Qur'an recitation therapy was administered for 30 minutes per session after the patient was positioned to relax and performed deep breathing relaxation. Nursing care was provided according to standard procedures. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS) before the intervention and for three consecutive days after therapy. The patient's initial anxiety score was 39 (severe anxiety). Care was provided from September 9 to 11, 2025, at RS-X Hospital in Malang. Results: The patient's initial anxiety level was in the severely anxious category with a HARS score of 39. After murottal therapy, the anxiety score decreased to 34 on the first day, 28 on the second day, and 19 on the third day, showing a gradual decrease from severe anxiety to mild anxiety. This intervention provided relaxation, emotional calm, and improved the patient's spiritual coping. Conclusion: Al-Qur'an murottal therapy has been proven effective in reducing anxiety levels in cancer patients through a relaxation mechanism that triggers the formation of endorphins, making the body feel calmer. Keywords: Al-Qur'an Murottal; Anxiety; Cervical Cancer; Complementary Therapy; HARS.